2008
DOI: 10.1097/pec.0b013e31817de130
|View full text |Cite
|
Sign up to set email alerts
|

Comparing the Frequency of Unrecognized Attention Deficit Hyperactivity Disorder Symptoms in Injured Versus Noninjured Patients Presenting for Care in the Pediatric Emergency Department

Abstract: Children presenting with injuries are no more likely than a noninjured age- and sex-matched group to have unrecognized ADHD based on parental screen. Targeting injured children for ADHD screening is not supported by this study.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 22 publications
0
5
0
Order By: Relevance
“…However, among school-aged pediatric patients, parental information on inattention and/or hyperactive-impulsive symptoms was cross-sectionally more often linked with hospital-treated injury than with appendicitis (Maxson, Lawson, Pop, Yuma-Guerrero, & Johnson, 2009) and more often with extremity fracture than with other orthopedic conditions (Uslu, Uslu, Eksioglu, & Ozen, 2007). On the other hand, clinically unrecognized symptoms of ADHD in children and adolescents were not associated with injuries treated in emergency department (Pittsenbarger, Grupp-Phelan, & Phelan, 2008). Even if neither ADHD nor oppositional defiant disorder (ODD) was separately associated with emergency department-treated injuries among preschoolers, the combination of these two conditions was associated with injury-risktaking behaviors (Garzon, Huang, & Todd, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…However, among school-aged pediatric patients, parental information on inattention and/or hyperactive-impulsive symptoms was cross-sectionally more often linked with hospital-treated injury than with appendicitis (Maxson, Lawson, Pop, Yuma-Guerrero, & Johnson, 2009) and more often with extremity fracture than with other orthopedic conditions (Uslu, Uslu, Eksioglu, & Ozen, 2007). On the other hand, clinically unrecognized symptoms of ADHD in children and adolescents were not associated with injuries treated in emergency department (Pittsenbarger, Grupp-Phelan, & Phelan, 2008). Even if neither ADHD nor oppositional defiant disorder (ODD) was separately associated with emergency department-treated injuries among preschoolers, the combination of these two conditions was associated with injury-risktaking behaviors (Garzon, Huang, & Todd, 2008).…”
Section: Introductionmentioning
confidence: 99%
“…In addition, Pittsenbarger, Grupp-Phelan, and Phelan (2008) ascertained that there was nothing to be gained from screening injured children presenting to the emergency department for ADHD symptoms, as the frequency of parent reported ADHD symptoms did not differ significantly between injured versus uninjured patients.…”
Section: Introductionmentioning
confidence: 99%
“…Another similarly found a double risk of having higher scores on the Conners' scale [8,19]. However, these results were challenged by another report, which showed that children visiting the ED with injuries were no more likely than non-injured children to have unrecognised ADHD, based on parental screening [9].…”
Section: Discussionmentioning
confidence: 96%
“…Accidents in children and adolescents are the most common cause of visits to the emergency department (ED) and among the leading causes of morbidity and mortality in Europe [3]. Previous studies suggest that children affected by ADHD are exposed to a higher risk of severe accidental injuries due to hyperactivity and decreased vigilance [6][7][8][9][10][11][12][13]. Moreover, evidence shows that early diagnosis and treatment significantly reduces ADHD related comorbidity [14,15].…”
Section: Introductionmentioning
confidence: 99%